كسور الكعبين المغلقة عند البالغين /النتائج الوظيفية لطرق العلاج المستخدمة في مشفى الأسد الجامعيّ في اللاذقـيّة / - سعد, معن; يوسف, صفوان; كشكش, عمار (Latakia University Journal -Medical Sciences Series, 2016)
شملت الدراسة 37 حالة كسر أحد الكعبين أو كليهما عند المرضى البالغين ممن راجعوا مشفى الأسد الجامعي في اللاذقية بين عام 2011 و 2014 . تراوحت أعمار المرضى بين 20 و 75 سنة , نسبة الذكور 54% . أكبر نسبة إصابة في الأعمار من 30 حتى 39 سنة (27%) . النسبة الأكبر لسبب الإصابة كانت بآلية الالتواء (8،56%) تلتها حوادث السير (29،7%) ثم أثناء الرياضة (13.5%) . نسبة كسر الكعبين المعزول تماثل نسبة كسر الكعب الأنسي المعزول (35،1%) ثمَّ الكعب الوحشي المعزول (29،8%) . عولجت 25 حالة جراحياً( 67،6%) ، بينما عولجت 12 حالة بشكل محافظ (32،4%) . كانت النتائج الوظيفية عند الذكور أفضل منها عند الإناث , و في الأعمار الشابة أفضل من الأعمار المتقدمة . كانت أفضل النتائج في العلاج الجراحي بنسبة (51،3%) و خاصة كسور الكعبين (21،6%) ، كانت أفضل النتائج للمرضى المعالجين بشكل محافظ في علاج كسر الكعب الأنسي المعزول (8،1%) بينما أسوء النتائج في الكعب الوحشي المعزول (5،4%) .The study included 37 cases of fractures of one or both isolated malleoluer in adult patients whose attended al-Assad University Hospital in Lattakia between 2011 and 2014. Patients' ages ranged between 20 and 75 years, the ratio of males was 54 % . Greatest range of injury in ages from 30 to 39 years old (27%) . The largest ratio of the mechanism of injury while was walking (56.8%), followed by traffic accidents (29.7%) and during sports (13.5%). Ratio of isolated malleoluer fractures is like the isolated medial malleolus (35.1%), and the isolated lateral malleolus is (29.8%). Surgically treated 25 cases (67.6%), while 12 cases were treated conservatively (32.4%). The functional results in males were better than in females, and in the younger ages were better than the older ages. The best results were in the surgical treatment by (51.3%), especially the isolated malleoluer fractures (21.6%), the best results for patients treated conservatively were in the treatment of isolated medial malleolus fracture (8.1%), while the worst results were in the isolated lateral malleolus (5.4%).